Pulmonary vein stenosis: Case report and literature review - Amin, R (Pulsus Group Inc, 2009)
BACKGROUND: Pulmonary vein stenosis is a rare cause of pulmonary hypertension, with variable onset and presentation. One or more of the four pulmonary veins can be primarily or secondarily affected. A five-month-old girl presented with respiratory distress, lethargy and cyanosis requiring intubation. METHODS: Echocardiography showed right ventricular dilation, a right ventricular systolic pressure of 97 mmHg, decreased ejection fraction and turbulent flow at the left atrium. Cardiac catheterization revealed stenosis of the left-sided pulmonary veins, for which she underwent a Coles procedure. RESULTS: Postoperatively, there was a transient improvement in the patient’s pulmonary hypertension but she subsequently deteriorated. Her prognosis was considered bleak, and a decision was made with the family to withdraw care. CONCLUSION: Pulmonary vein stenosis is a rare cause of pulmonary hypertension, and is associated with significant morbidity and mortality. Surgical intervention may be of benefit in selected cases. It stands to reason that any treatment will have the best chance of success if completed before the pulmonary hypertension becomes fixed. Early diagnosis depends on a high index of clinical suspicion.